Genetic polymorphisms and sepsis in premature neonates. - Susanna Esposito (Public Library of Science (PLoS), 2014)
Identifying single nucleotide polymorphisms (SNPs) in the genes involved in sepsis may help to clarify the pathophysiology of neonatal sepsis. The aim of this study was to evaluate the relationships between sepsis in pre-term neonates and genes potentially involved in the response to invasion by infectious agents. The study involved 101 pre-term neonates born between June 2008 and May 2012 with a diagnosis of microbiologically confirmed sepsis, 98 pre-term neonates with clinical sepsis and 100 randomly selected, otherwise healthy pre-term neonates born during the study period. During the study, 47 SNPs in 18 candidate genes were genotyped on Guthrie cards using an ABI PRISM 7900 HT Fast real-time and MAssARRAY for nucleic acids instruments. Genotypes CT and TT of rs1143643 (the IL1β gene) and genotype GG of rs2664349GG (the MMP-16 gene) were associated with a significantly increased overall risk of developing sepsis (p = 0.03, p = 0.05 and p = 0.03), whereas genotypes AG of rs4358188 (the BPI gene) and CT of rs1799946 (the DEFβ1 gene) were associated with a significantly reduced risk of developing sepsis (p = 0.05 for both). Among the patients with bacteriologically confirmed sepsis, only genotype GG of rs2664349 (the MMP-16 gene) showed a significant association with an increased risk (p = 0.02). Genotypes GG of rs2569190 (the CD14 gene) and AT of rs4073 (the IL8 gene) were associated with a significantly increased risk of developing severe sepsis (p = 0.05 and p = 0.01). Genotype AG of rs1800629 (the LTA gene) and genotypes CC and CT of rs1341023 (the BPI gene) were associated with a significantly increased risk of developing Gram-negative sepsis (p = 0.04, p = 0.04 and p = 0.03). These results show that genetic variability seems to play a role in sepsis in pre-term neonates by influencing susceptibility to and the severity of the disease, as well as the risk of having disease due to specific pathogens.